The Effectiveness of Instagram Social Media as a Promotional Media at Bali Zoo Gianyar Tourist Attraction - Widyantara, I Made Sugi; Mertha, I Wayan; Widana, Ida Bagus Gede Agung (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Bali Zoo Gianyar tourist attraction is one of the tourist attractions that uses social media, especially Instagram as a promotional medium, therefore it is very important to know the effectiveness of social media in promoting a tourist attraction. The purpose of this study was to determine the effectiveness of Instagram social media as a promotional medium for Bali Zoo Gianyar tourist attraction. The respondents used were 100 domestic tourists with a quantitative approach with the AIDA analysis model. The results of this study show the Attention dimension (effectiveness = 75.6%); Interest dimension (effectiveness = 78.6%); Desire dimension (effectiveness = 68.5%); and Action dimension effectiveness = 68.1%). From the percentage results for each AIDA dimension, Instagram social media @BaliZoo is effective as a promotional medium for Bali Zoo Gianyar Tourist Attraction.